Bisphosphonates and osteonecrosis of the jaws - Szyszkowska, Anna; Puławska, Marta; Karczmarek-Borowska, Bożenna (Contemporary Oncology/Współczesna Onkologia, 2008)
Bisphosphonates show a high affinity to calcium. They are absorbed by the hydroxyapatites and permanently built into bone structure. More and more frequently a diagnosed complication in patients treated protractedly with bisphosphonates is osteonecrosis of the jaws. A number of cases concerning patients who have suffered from jaw osteonecrosis after receiving bisphosphonate therapy have recently been published. The purpose of these documents is to assess risk factors and clinical picture as well as provide guidelines on prevention, recognition and treatment of jaw osteonecrosis after taking bisphosphonates. It is of great importance to take into account the risk of jaw osteonecrosis occurance in patients with a long-standing treatment with bisphosphonates. It is recommended to make a thorough dental examination and a complete heal of pathologies founded in the oral cavity before starting bisphosphonate therapy.